Iranian and Israeli Infiltration in Africa and Its Implications for the Arab World: A Comparative Study - Qerbaa, Mohammad Khair; Hammad, Abdelsalam Atyah (Dirasat: Human and Social Sciences, 2023)
Objectives: This study investigates Iranian and Israeli infiltration in Africa and its implications for the Arab world. It examines the impacts and mechanisms involved in such infiltration. Methods: The study employs historical, descriptive, analytical, and comparative approaches. It traces the process of penetration from its initial stages to subsequent extensions, defining and describing the characteristics of this infiltration. It analyzes its components, and highlights similarities and differences in the infiltration process. Results: The study yielded the following results: Political, economic, and strategic goals, as well as security-related goals, are pursued by both Israeli and Iranian infiltration in Africa. Their specific goals include hindering Palestine from gaining international acknowledgment of its presence and attracting foreign investments to Iran. Additionally, the study identified the mechanisms employed by Israel and Iran for infiltration in Africa, such as creating diplomatic relationships between Israel and African countries, establishing embassies, and establishing a military base near the borders of Djibouti. Conclusions: In conclusion, it is crucial to enhance cooperation and coordination with African countries across various domains while simultaneously strengthening security and strategic partnerships among Arab nations, particularly Egypt, Saudi Arabia, and Sudan. This collective effort aims to effectively counter the threat posed by Iranian infiltration in Africa.